A time for drunken horses [videorecording (DVD)] - Ghobadi, Bahman; Ahmadi, Ayoub; Younessi, Rojin; Ekhtiar-Dini, Amaneh (Lorber Films, 2011)
After their father dies, a family of five is forced to survive on their own in a Kurdish village on the border of Iran and Iraq. Matters are made worse when twelve-year-old Ayoub, the new head of the family, is told that his handicapped brother Madi needs an immediate operation in order to remain alive. The family must go to any length to survive in the harshest of conditions, where even the horses are fed liquor to get them to work.